Always Check the Lead!… Unique Case of Cardiac Arrest Due to Pacemaker Infective Endocarditis (Archives of Clinical and Medical Case Reports, 2021)
53-year-old patient with multiple recurrent admissions for chest pain and low-grade fever presented after recent discharge for the same complaint. In his previous admission, cardiac work-up was done with no significant findings and he was discharged on oral antibiotics. However, upon this admission he developed cardiac arrest due to ventricular fibrillation and was intubated. Upon further assessment and intervention, he was found to have Pacemaker-lead-wire infective endocarditis. We share this interesting case as Infective endocarditis could present as a vague symptom that needs further intervention.